The Influence of Javanese Dialect on Students’ Ability in Learning English Pronunciation at Second Year of Social Program Students in MAN Cirebon 1 - Aditiya Firmansyah (Papanda Publisher, 2022)
One of languages in Indonesia that has many variety is javenese language. The Javanese language is part of the Austronesia family, and is therefore related to Indonesian and other Malay varieties. Many speakers of Javanese also speak Indonesian for official and commercial purposes and to communicate with non-Javanese Indonesians. There are three main groups of Javanese dialects based on the sub region where the speakers live. They are: Western Javanese, Central Javanese and Eastern Javanese. The aims of the research carried out by the writer are to find out the data about the Javanese dialect, to find out the students’ ability in learning English pronunciation, and to find out the influence of Javanese dialect on the students’ ability in Learning English Pronunciation. The technique of collecting data is observation, interview, questioner, and test. The quantitative data are analyzed by using t-test formula and DC formula. After the data have been analyzed, the writer concludes that the Influence between X and Y variable is strong or high and the degree of freedom (df) is 28, with the significance 5% it shows that the critical value of t-test is 2.05. Based on the calculation of DC, the writer gets 0,8064% that influence of X variable gives contribution to the Y variable. Because the value of tobserve is higher than the critical value of the t-table with the significance 5% (2.05), it means that using Javanese dialect has strong or high influence to students’ ability in English pronunciation.